2014
DOI: 10.4049/jimmunol.1201558
|View full text |Cite
|
Sign up to set email alerts
|

The Lupus Susceptibility Locus Sle1 Facilitates the Peripheral Development and Selection of Anti-DNA B Cells through Impaired Receptor Editing

Abstract: Systemic lupus erythematosus is characterized by the spontaneous production of IgG autoantibodies in patients and lupus-prone mice. In this study, we investigated the effect of the Sle1 lupus susceptibility locus on the peripheral development of 56R+ anti-DNA transgenic B cells by tracking 56R+ B cells in mice without (B6.56R) or with (B6.Sle1.56R) the Sle1 locus. Compared with B6.56R mice, B6.Sle1.56R mice exhibited increased class-switched IgG2a anti-DNA Abs in their serum, encoded by the transgene. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To assess receptor editing more directly, we quantified the frequency of the VκRS rearrangement sequence within pre–B cells, which forms within the Igκ light chain locus following exhaustive editing (15). Compared to empty vector treatment, IFNα‐treated mice displayed a significant decrease in the relative abundance of the VκRS rearrangement sequence (Figure 2D), consistent with impaired receptor editing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess receptor editing more directly, we quantified the frequency of the VκRS rearrangement sequence within pre–B cells, which forms within the Igκ light chain locus following exhaustive editing (15). Compared to empty vector treatment, IFNα‐treated mice displayed a significant decrease in the relative abundance of the VκRS rearrangement sequence (Figure 2D), consistent with impaired receptor editing.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, purified genomic DNA (15–25 ng) was mixed with SYBR‐green master mix (Thermo Fisher Scientific) and 1 μ M primers in a 20 μl reaction volume. Cycling conditions were as follows: 95°C for 15 minutes, followed by 50 cycles at 95°C for 15 seconds, 60°C for 15 seconds, and 72°C for 30 seconds, using the same primers as previously reported (15). The amount of VκRS product in each sample was normalized to the amount of β‐actin product and then compared with the normalized value for uninfected B6 B220+IgM+Igκ+ B cells to determine relative quantity.…”
Section: Methodsmentioning
confidence: 99%
“…This has been observed in multiple animal models and can be inferred in humans and mice by the loss of some, though not all, autoAbs after B cell depletion therapy (7-10). Most prominently, anti-DNA and anti-self-IgG (rheumatoid factor, RF) responses use the EF pathway (11, 12). In contrast to the GC, how these EF responses are promoted and regulated is poorly defined, both in immunity and autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…Sle1 expression decreased the percentage and number of total B cells but favored the expansion of AM14 HC tg B cells over endogenous B cells, and this was independent of the expression of the autoAg. Consistent with this result, it has been shown that Sle1 locus favored the expansion of DNA-specific 56R HC tg B cells relative to the endogenous B cells [34]. In the AM14 model, the expansion of the tg B cells resulted in a relatively low production of antichromatin IgG2a a by endogenous B cells, thereby limiting autoAg availability for Id + RF B cells.…”
Section: Discussionmentioning
confidence: 63%